Peran Resiliensi dalam Hubungan Self-compassion dan Psychological Well-Being pada Mahasiswa dengan Tradisi Bapukung - Norhidayah, Meininda Rhivent; Efendy, Mamang; Pratikto, Herlan (Personifikasi: Jurnal Ilmu Psikologi, 2025)
Psychological well-being is essential for mental health and academic success; however, the role of self-compassion and resilience in the local cultural context remains underexplored. This study examines the relationship between self-compassion and psychological well-being, with resilience as a mediator, among students with a background in the bapukung tradition in South Kalimantan. A quantitative research method was employed using purposive sampling, involving 273 students from a total population of 89,980. Data analysis was conducted using path analysis to examine the mediating role of resilience in the relationship between self-compassion and psychological well-being. The findings indicate that self-compassion positively influences psychological well-being, both directly and indirectly through resilience as a partial mediator. This suggests that self-compassion enhances psychological well-being not only directly but also by strengthening individual resilience. The results highlight that while the bapukung tradition contributes to early emotional bonding, it is insufficient to enhance psychological well-being in adulthood. Therefore, additional interventions, such as education and counseling, focusing on strengthening self-compassion and resilience, are needed to optimally support students' psychological well-being.